Design and Synthesis of Novel Bis Thiazolo[4,5-c]Isoxazolines Bearing 1,2,4-triazole Ring Derived From the Related 4-thiazolidinons as Antimicrobial Agents - Ayyash, Ahmed Neamah (Iraqi Journal of Science, 2023)
Design and synthesis of novel poly heterocycles together using same heterocyclic compound is the main task of the present paper. The target compounds entitled 4,4’-[benzene-1,4-diylbis[ethylidenehydrazine-2-ylidene]bis[4-[3,5-di(5-substitutedpyridin-2-yl)-3,3a-dihydro[1,3]thiazolo[4,5-c][1,2]oxazol-6(5H)-yl]-4H-3-yl-1,2,4-triazole-3-thiol] have been synthesized starting from the reaction of 1,4-diacetylphenyl and carbohydrazide to give Schiff base derivatives then 1,2,4- triazole derivatives from the reaction with CS2 and an excess of hydrazine hydrate. The same applies for the condensing of these newly heterocyclic amines with different pyridine-2-carbaldehydes, which resulted in the synthesis of some new Schiff bases, which were then cyclized to develop new thiazolidinones by thioglycolic acid. Additionally, by fusing thiazolidinones with various pyridine-2-carbaldehydes, a novel chalcone was formed. To produce the desired fused isoxazolines, the later compounds underwent cyclization with hydroxylamine hydrochloride and potassium hydroxide. From the examination of the (CHN), FTIR, 1H NMR, and 13C NMR spectra, the structural identities of all recently synthesized compounds were determined. The newly synthesized chemicals were also successfully tested as an antibacterial agent.